The Impact of Partnership Programs on Coffee Farm Performance: A Propensity Score Matching Analysis from Lampung Province, Indonesia - Prasmatiwi, Fembriarti Erry; Sayekti, Wuryaningsih Dwi; Lestari, Dyah Aring Hepiana; Adawiyah, Rabiatul; Sari, Dewi Mulia; Astuti, Tri Novi (Research on World Agricultural Economy, 2026)
Global coffee consumption is increasing by 1–2% per year, making coffee a commodity with a growing market. More than 60% of the worldwide coffee supply depends on small farmers. However, small-scale coffee farmers still struggle with issues related to low coffee productivity and quality, as well as limited market access, which affect their farming performance. This study identifies critical variables that influence farmers' propensity to participate in partnerships and analyzes the impact of their participation on coffee farming performance. The Propensity Score Matching Method determines how agricultural producers can be classified as either partner farmers or non-partner farmers due to formal relationships between them or other factors. The data used for this analysis were obtained from a survey of 230 coffee farmers in three main sub-districts of Central Tanggamus. The survey included 126 partner farmers and 104 non-partner farmers. It was determined that farmer participation in partnerships was based on educational attainment, farmers' previous farming experience, the distances between the homes of farmers and their agricultural fields, and the sizes of their farms. Moreover, the partnership program increased coffee productivity by 22.29%, land productivity by 22.72%, reduced farming costs by 7.46%, and increased selling prices by 4.06%, thereby increasing farm income by 47.79% and land income by 47.51%. The findings indicate that the partnership program increases coffee productivity and creates cost efficiencies, thereby simultaneously improving agricultural economic performance. Therefore, these findings support the expansion of partnership programs that take into account the sociodemographic characteristics of participating farmers. ER